O jornal sindical e a formação política: o caso da Udemo junto aos diretores de escola da rede estadual paulista - Lança, Hélida (2013)
The (in)formative action embodied in the newspaper O Diretor (The Principal) is the object of analysis of this research, which aims to understand how UDEMO (Union of the Education Specialists of the Official Professorship of São Paulo State) carries out political formation by the means of its news paper, an important tool of communication with its base. This study analyzed the issues of O Diretor published during five years, starting in September 2007 when São Paulo faz Escola program was released and stablished a new model of education and management for the paulista state schools. Initially, we approach the education reform and the new characteristics of the management it intends. Next, we approach UDEMO's trajectory in the context of teaching unions, as well as the union press possibilities of political formation of its members. Drawing on a Marxist conception of human formation, on a third moment we present the path taken and the theoretical bases of this study, as well as the literature review. In the last chapter, the presentation of the data collected and the development of the analysis about the O Diretor sections. The findings demonstrate that UDEMO has been exempting themselves from the discussion about the most candescent and substantive issues of the model of education and management adopted by the governmental policy, centralizing the revendications and the debate on issues of specific interest to school principals of that schooling system.